2018
DOI: 10.1007/s10616-017-0181-5
|View full text |Cite
|
Sign up to set email alerts
|

Culture in embryonic kidney serum and xeno-free media as renal cell carcinoma and renal cell carcinoma cancer stem cells research model

Abstract: The use of fetal bovine serum hinders obtaining reproducible experimental results and should also be removed in hormone and growth factor studies. In particular hormones found in FBS act globally on cancer cell physiology and influence transcriptome and metabolome. The aim of our study was to develop a renal carcinoma serum free culture model optimized for (embryonal) renal cells in order to select the best study model for downstream auto-, para- or endocrine research. Secondary aim was to verify renal carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The growth of renal cancer and renal cancer stem cells in in vitro conditions requires optimal stability between signals mediating proliferation, cell survival and self-renewal. For in vitro application of RCC, the use of completely defined conditions and elimination of animal-derived materials from the culture is recommended (Krawczyk et al 2018 ). Therefore, we aimed to develop the most efficient animal serum free culture system for RCC experiments through comparing available stable RCC cell lines and verifying different culture media.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of renal cancer and renal cancer stem cells in in vitro conditions requires optimal stability between signals mediating proliferation, cell survival and self-renewal. For in vitro application of RCC, the use of completely defined conditions and elimination of animal-derived materials from the culture is recommended (Krawczyk et al 2018 ). Therefore, we aimed to develop the most efficient animal serum free culture system for RCC experiments through comparing available stable RCC cell lines and verifying different culture media.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has revealed that the addition of specific serum under specific conditions during the extraction of MSCs or the enrichment of tumor stem cells can have a positive effect [ 18 20 ]. It has also been shown that it is entirely possible to cultivate CSCs from serum-containing media [ 21 , 22 ]. In this study, we cultured HCT116 in ultra-low adhesion plates with serum-free medium containing EGF, FGF-2, and B-27.…”
Section: Introductionmentioning
confidence: 99%